Analysis of Physical Components of the Smash Ability of the Volleyball Extracurricular Game at SMA Negeri 16 Makassar - Achmad Karim (CV Lentera Cendekia Indonesia, 2026)
This study aims to determine: (1) whether there is a relationship between hand-eye coordination and volleyball smashing ability in the extracurricular activities of SMA Negeri 16 Makassar; (2) whether there is a relationship between leg muscle explosiveness and volleyball smashing ability in the extracurricular activities of SMA Negeri 16 Makassar; (3) whether there is a relationship between arm muscle explosiveness and volleyball smashing ability in the extracurricular activities of SMA Negeri 16 Makassar; (4) whether there is a relationship between hand-eye coordination, leg muscle explosiveness, and arm muscle explosiveness collectively and volleyball smashing ability in the extracurricular activities of SMA Negeri 16 Makassar. This study is a correlational study. The method used is quantitative, with data collection techniques using tests and measurements. The population of this study was the entire extracurricular activities of SMA Negeri 16 Makassar. The sample used was 30 volleyball extracurricular students. The data analysis techniques used in this study were descriptive analysis, correlation analysis, and regression analysis at a significance level of α = 0.05 using SPSS. The results of the study show that: (1) There is a significant relationship between hand-eye coordination and smash ability in volleyball with a value of r = 0.791 (p < α = 0.05); (2) There is a significant relationship between leg muscle explosive power and smash ability in volleyball with a value of r = 0.786 (p < α = 0.05); (3) There is a significant relationship between arm muscle explosive power and smash ability in volleyball with a value of r = 0.791 (p < α = 0.05); (4) There is a significant relationship between hand-eye coordination, leg muscle explosive power and arm muscle explosive power together with smash ability in volleyball with a determination coefficient value of R2 = 0.756 (p < α = 0.05).